Onto Semantic Tourism Information Retrieval - S. Laddha, Shilpa; Pradip M. Jawandhiya, Dr. (International Journal of Engineering and Technology, 2018)
Semantic Search is an area of research which focuses on meaning of terms used in user query. Ontology plays significant role to define the concept and the relationship of terms in domain. Since the understanding of concepts is domain specific, Ontology creation is also domain specific. According to this argument, query interpreted in Tourism domain can have different meaning in some other domain. This paper presents a prototype of information retrieval interface using ontology which can save users time by rendering relevant, precise and efficient search results as compared to traditional search interfaces.Â Â